Students’ Perspective on Online Learning during Covid–19 Pandemic - Sri Rahmadhani Siregar (English Education : English Journal for Teaching and Learning, 2022)
Pandemic Covid-19 has successfully forced the world shutdown several activities including educational activities. The educational system in Indonesia has been in change since the covid-19 pandemic spread across the country. Face-to-face learning is quickly being replaced by virtual learning. In this study researcher would like to know the students’ perspective on Online Learning during Covid–19 Pandemic. This research used qualitative descriptive method. The subjects of this research were the students at grade XI in 2019/2020 academic year at SMAN 2 Plus Sipirok. The research instruments were questionnaire that was described response to know their perspective in using online learning. The result identified student got problems and difficulties in conducting online learning because it was not effective. The students prefer face to face learning than by using WhatApp and Zoom application.